2018
DOI: 10.1016/j.exer.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiology of the corneal epithelium

Abstract: There has been a drive to develop new cell based therapies to treat corneal blindness, one of the most common causes of blindness worldwide. Mechanical and physical cues are known to regulate the behavior of many cell types, however studies examining these effects on corneal epithelial cells have been limited in number and their findings have not previously been amalgamated and contrasted. Here, we provide an overview of the different types of mechanical stimuli to which the corneal epithelium is exposed and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 107 publications
3
50
0
1
Order By: Relevance
“…The scaffolds must be sufficiently stiff and strong to be able to withstand suturing without tearing and withstand physiological forces applied to it postimplantation such as intraocular pressure, eyelid motion, and tear film motion. [44] If the scaffold is insufficiently stiff or strong, it could undergo deformation or failure, respectively. The scaffold stiffness should also not be too high, as this would reduce its ability to deform in the same way as the surrounding tissue when under stress and potentially lead to a mismatch in strain.…”
Section: Scaffold Physical Propertiesmentioning
confidence: 99%
“…The scaffolds must be sufficiently stiff and strong to be able to withstand suturing without tearing and withstand physiological forces applied to it postimplantation such as intraocular pressure, eyelid motion, and tear film motion. [44] If the scaffold is insufficiently stiff or strong, it could undergo deformation or failure, respectively. The scaffold stiffness should also not be too high, as this would reduce its ability to deform in the same way as the surrounding tissue when under stress and potentially lead to a mismatch in strain.…”
Section: Scaffold Physical Propertiesmentioning
confidence: 99%
“…The role of tissue biomechanics in corneal function, and in particular as a regulator of LESC behavior, has been the focus of growing research in the past decade. 49 Studies using contact 50 and non-contact 51 analytical tools have demonstrated that the corneal limbus represents a biomechanical niche distinct from its central region. Specifically, the high-resolution characterization of corneal biomechanics shows that the matrix supporting epithelial cells in the limbus is significantly more heterogeneous compared with that supporting the central epithelium, and is comprised of numerous pockets with significantly lower elastic modulus associated with LESC residency.…”
Section: Corneal Biomechanics In Health and Diseasementioning
confidence: 99%
“…Moreover, epithelial stem cell therapies have largely ignored the niche and focused on cell populations to be transplanted, and this neglect leads to a lack of control over stem cell behavior that may contribute to the high failure rates of cell therapies. [ 8–10 ] In addition to mechanical cues, we hypothesized that spatial geometry plays a crucial role in determining stem cell fate. Our aim was to recreate the precise geometry of an epithelial stem cell niche using two‐photon polymerization (2PP) and to determine the role of spatial geometry on stem cell phenotype in a 3D microniche setting.…”
Section: Figurementioning
confidence: 99%